Sectoral FDI inflows and domestic investments in Pakistan - Shah, Syed Hasanat (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2020)
In this paper, for the first time, we analyze the relation of sectoral FDI with domestic investment in Pakistan by using ARDL cointegration technique over a period of 1980–2012. Empirical findings show that aggregate FDI crowd in domestic investment, however, the effects of aggregate FDI on domestic investment in Pakistan cannot be generalized. The impact of FDI on domestic investment varies across sectors. The empirical findings in the study at sectoral level suggests that FDI in manufacturing and services sectors crowd in domestic investment while FDI in primary sector assert insignificant impact on domestic investment in Pakistan. Analyzing the reverse causal impact running from domestic investment to FDI, this study confirm that domestic investment is important in attracting FDI across the board in all the three sectors i.e. primary, manufacturing and services sectors. The positive role of FDI in manufacturing and services sectors and supportive role of indigenous investment infrastructure is of utmost importance for FDI to promote domestic investment in Pakistan.